Efficacy of QR678 Neo® hair growth factor formulation for the treatment of hair loss in Covid‐19‐induced persistent Telogen Effluvium—A prospective, clinical, single‐blind study. (7th December 2021) - Shome, Debraj; Kapoor, Rinky; Surana, Monika; Vadera, Sapna; Shah, Ronak
Abstract: Background: Telogen Effluvium (TE) in a post‐Covid‐19 patient causes excessive shedding of hair. No definite treatment is available till now. Past studies demonstrates that QR678Neo ® has shown promising results in various types of Alopecia. Aim: In this study, we aim to establish efficacy of QR678 Neo ® hair growth factor formulation administration in Covid‐19‐induced persistent TE for treatment of hair loss and for hair regrowth. Material & Method: Twenty adult patients (all females) presenting with persistent TE starting few weeks after recovery from Covid‐19 infection, and continuing beyond 6 months were included for the study. A 1.5 mL solution of QR678 Neo ® hair growth factor formulation was administered in the scalp per session. A total of 8 sessions (one session every 4 weeks) were done. The results were assessed at the baseline, after 4thsession, and 1 month after 8th session. Results: Most of the patients showed significant reduction in hair fall; 89% patients showed excellent hair growth. Global photographic assessment score showed marked improvement, which maintained even post therapy. Videomicroscopic assessment showed increase in the hair count (mean =29.32) after 8th session, that further improved even post therapy. The subjective assessment scores for overall hair growth, appearance of hair, reduction in visibility of the scalp, and hair loss were 4, 4.5, 4.25, and 5, respectively. Conclusion: Management of Covid‐19‐induced persistent Telogen Effluvium has been unclear and futile so far. Intra‐dermal administration of QR678 Neo ® hair growth factor formulation in the scalp, reduces hair fall, improves hair regrowth, and increases the hair density.